Emotional engagement in feature film storytelling : reframing the classical three-act structure / Norlela Ismail - Ismail, Norlela (UPENA, 2006)
This article examines the contributions of the classical three-act structure in storytelling that could evoke emotions. The importance of its relationship with character's goal, motivation and audience's emotion is also discussed. A case study is ^employed as a research method in which Field and McKee's conception of the three-act paradigm is used to analyse the case. The purpose of this article is to provide a platform (not offering a formula) for a filmmaker or screenwriter to emulate an approach that could help obtain an emotionally engaging story.